Effect of Drying Time on Physicochemical Characteristics of Dragon Fruit Peels Powder (Hylocereus polyrhizus) - Qalbi, Rainatul; Giovani, Sarah; Guo, Qiyong; Adelina, Nadya Mara (Journal of Agri-Food Science and Technology, 2023)
The increasing production and demand of dragon fruit (Hylocereus polyrhizus) in Indonesia produces a high amount of dragon fruit peel waste that can pollute the environment. As an alternative, dragon fruit peel could be applied as a functional food ingredient due to its high fiber content and antioxidant capacity. This study contributed to analyzing the effect of drying time on the physical and chemical characteristics of dragon fruit peel powder. To optimize the functional properties, dragon fruit peel was developed into a powder that was prepared by using a food dehydrator at 60 °C with drying times of 4, 5, and 6 h. The results showed that the longer drying time led to lower moisture and protein content, which reached the lowest at 9.73% and 13.07% with a drying time of 6 h, respectively. Meanwhile, drying time (4-6 h) did not significantly affect the ash (13.74-14.57%), fat (22.46-23.46%), and crude fiber content (29.13-31.75%) of dragon fruit peel powder. The drying time can affect antioxidant activity significantly, while the highest antioxidant activity was found in 6 h drying time (IC50 0.03 gram/mL). The L* value was measured between 29.68-30.23, a* value 9.61-10.34, and b* value 15.20-16.53. The drying time of 4 h could maintain the color of dragon fruit peel and produce the highest yield product at 4.52%. In general, drying dragon fruit peel powder for 4 hours gave the best results for high fiber content and high yield. Drying it for 6 hours was suggested to increase its antioxidant activity.